1968 : today's authors explore a year of rebellion, revolution, and change - Aronson, Marc; Bartoletti, Susan Campbell (Candlewick Press, 2019)
Provides an anthology of nonfiction writing from fourteen authors that offer insight in the tumultuous year of 1968, which saw the Vietnam War, assassinations, and anti-establishment protests all over the world. Features memoirs, personal essays, narratives, and travel writing.